Nup153 interacts with Sox2 to enable bimodal gene regulation and maintenance of neural progenitor cells - Toda, Tomohisa; Hsu, Jonathan Y.; Linker, Sara B.; Hu, Lauren; Schafer, Simon T.; Mertens, Jerome; Jacinto, Filipe V.; HETZER, Martin W; Gage, Fred H. (Cell Stem Cell)
Neural progenitor cells (NeuPCs) possess a unique nuclear architecture that changes during differentiation. Nucleoporins are linked with cell-type-specific gene regulation, coupling physical changes in nuclear structure to transcriptional output; but, whether and how they coordinate with key fate-determining transcription factors is unclear. Here we show that the nucleoporin Nup153 interacts with Sox2 in adult NeuPCs, where it is indispensable for their maintenance and controls neuronal differentiation. Genome-wide analyses show that Nup153 and Sox2 bind and co-regulate hundreds of genes. Binding of Nup153 to gene promoters or transcriptional end sites correlates with increased or decreased gene expression, respectively, and inhibiting Nup153 expression alters open chromatin configurations at its target genes, disrupts genomic localization of Sox2, and promotes differentiation in vitro and a gliogenic fate switch in vivo. Together, these findings reveal that nuclear structural proteins may exert bimodal transcriptional effects to control cell fate.
Keywords: Cell Biology; Genetics; Molecular Medicine

A slow conformational switch in the BMAL1 transactivation domain modulates circadian rhythms - Gustafson, Chelsea L.; Parsley, Nicole C.; Asimgil, Hande; Lee, Hsiau-Wei; Ahlbach, Christopher; Michael, Alicia Kathleen; Xu, Haiyan; Williams, Owen L.; Davis, Tara L.; Liu, Andrew C.; Partch, Carrie L. (Molecular Cell)
The C-terminal transactivation domain (TAD) of BMAL1 (brain and muscle ARNT-like 1) is a regulatory hub for transcriptional coactivators and repressors that compete for binding and, consequently, contributes to period determination of the mammalian circadian clock. Here, we report the discovery of two distinct conformational states that slowly exchange within the dynamic TAD to control timing. This binary switch results from cis/trans isomerization about a highly conserved Trp-Pro imide bond in a region of the TAD that is required for normal circadian timekeeping. Both cis and trans isomers interact with transcriptional regulators, suggesting that isomerization could serve a role in assembling regulatory complexes in vivo. Toward this end, we show that locking the switch into the trans isomer leads to shortened circadian periods. Furthermore, isomerization is regulated by the cyclophilin family of peptidyl-prolyl isomerases, highlighting the potential for regulation of BMAL1 protein dynamics in period determination.
Keywords: Cell Biology; Molecular Biology

Nuclear envelope rupture is induced by actin-based nucleus confinement - Hatch, Emily M.; HETZER, Martin W (Journal of Cell Biology)
Repeated rounds of nuclear envelope (NE) rupture and repair have been observed in laminopathy and cancer cells and result in intermittent loss of nucleus compartmentalization. Currently, the causes of NE rupture are unclear. Here, we show that NE rupture in cancer cells relies on the assembly of contractile actin bundles that interact with the nucleus via the linker of nucleoskeleton and cytoskeleton (LINC) complex. We found that the loss of actin bundles or the LINC complex did not rescue nuclear lamina defects, a previously identified determinant of nuclear membrane stability, but did decrease the number and size of chromatin hernias. Finally, NE rupture inhibition could be rescued in cells treated with actin-depolymerizing drugs by mechanically constraining nucleus height. These data suggest a model of NE rupture where weak membrane areas, caused by defects in lamina organization, rupture because of an increase in intranuclear pressure from actin-based nucleus confinement.
Keywords: Cell Biology

Directly reprogrammed human neurons retain aging-associated transcriptomic signatures and reveal age-related nucleocytoplasmic defects - Mertens, Jerome; Paquola, Apuã C.M.; Ku, Manching; Hatch, Emily; Böhnke, Lena; Ladjevardi, Shauheen; McGrath, Sean; Campbell, Benjamin; Lee, Hyungjun; Herdy, Joseph R.; Gonçalves, J. Tiago; Toda, Tomohisa; et al. (Cell Stem Cell)
Aging is a major risk factor for many human diseases, and in vitro generation of human neurons is an attractive approach for modeling aging-related brain disorders. However, modeling aging in differentiated human neurons has proved challenging. We generated neurons from human donors across a broad range of ages, either by iPSC-based reprogramming and differentiation or by direct conversion into induced neurons (iNs). While iPSCs and derived neurons did not retain aging-associated gene signatures, iNs displayed age-specific transcriptional profiles and revealed age-associated decreases in the nuclear transport receptor RanBP17. We detected an age-dependent loss of nucleocytoplasmic compartmentalization (NCC) in donor fibroblasts and corresponding iNs and found that reduced RanBP17 impaired NCC in young cells, while iPSC rejuvenation restored NCC in aged cells. These results show that iNs retain important aging-related signatures, thus allowing modeling of the aging process in vitro, and they identify impaired NCC as an important factor in human aging.
Keywords: Cell Biology; Genetics; Molecular Medicine

Integrated transcriptome and proteome analyses reveal organ-specific proteome deterioration in old rats - Ori, Alessandro; Toyama, Brandon H.; Harris, Michael S.; Bock, Thomas; Iskar, Murat; Bork, Peer; Ingolia, Nicholas T.; HETZER, Martin W; Beck, Martin (Cell Systems)
Aging is associated with the decline of protein, cell, and organ function. Here, we use an integrated approach to characterize gene expression, bulk translation, and cell biology in the brains and livers of young and old rats. We identify 468 differences in protein abundance between young and old animals. The majority are a consequence of altered translation output, that is, the combined effect of changes in transcript abundance and translation efficiency. In addition, we identify 130 proteins whose overall abundance remains unchanged but whose sub-cellular localization, phosphorylation state, or splice-form varies. While some protein-level differences appear to be a generic property of the rats’ chronological age, the majority are specific to one organ. These may be a consequence of the organ’s physiology or the chronological age of the cells within the tissue. Taken together, our study provides an initial view of the proteome at the molecular, sub-cellular, and organ level in young and old rats.
Keywords: Cell Biology; Histology; Pathology and Forensic Medicine

The nucleoporin gp210/Nup210 controls muscle differentiation by regulating nuclear envelope/ER homeostasis - Gomez-Cavazos, J. Sebastian; HETZER, Martin W (Journal of Cell Biology)
Previously, we identified the nucleoporin gp210/Nup210 as a critical regulator of muscle and neuronal differentiation, but how this nucleoporin exerts its function and whether it modulates nuclear pore complex (NPC) activity remain unknown. Here, we show that gp210/Nup210 mediates muscle cell differentiation in vitro via its conserved N-terminal domain that extends into the perinuclear space. Removal of the C-terminal domain, which partially mislocalizes gp210/Nup210 away from NPCs, efficiently rescues the differentiation defect caused by the knockdown of endogenous gp210/Nup210. Unexpectedly, a gp210/Nup210 mutant lacking the NPC-targeting transmembrane and C-terminal domains is sufficient for C2C12 myoblast differentiation. We demonstrate that the endoplasmic reticulum (ER) stress-specific caspase cascade is exacerbated during Nup210 depletion and that blocking ER stress-mediated apoptosis rescues differentiation of Nup210-deficient cells. Our results suggest that the role of gp210/Nup210 in cell differentiation is mediated by its large luminal domain, which can act independently of NPC association and appears to play a pivotal role in the maintenance of nuclear envelope/ER homeostasis.
Keywords: Cell Biology

The chromatin remodeler SPLAYED negatively regulates SNC1-mediated immunity - Johnson, Kaeli C.M.; Xia, Shitou; Feng, Xiaoqi; Li, Xin (Plant and Cell Physiology)
SNC1 (SUPPRESSOR OF NPR1, CONSTITUTIVE 1) is one of a suite of intracellular Arabidopsis NOD-like receptor (NLR) proteins which, upon activation, result in the induction of defense responses. However, the molecular mechanisms underlying NLR activation and the subsequent provocation of immune responses are only partially characterized. To identify negative regulators of NLR-mediated immunity, a forward genetic screen was undertaken to search for enhancers of the dwarf, autoimmune gain-of-function snc1 mutant. To avoid lethality resulting from severe dwarfism, the screen was conducted using mos4 (modifier of snc1, 4) snc1 plants, which display wild-type-like morphology and resistance. M2 progeny were screened for mutant, snc1-enhancing (muse) mutants displaying a reversion to snc1-like phenotypes. The muse9 mos4 snc1 triple mutant was found to exhibit dwarf morphology, elevated expression of the pPR2-GUS defense marker reporter gene and enhanced resistance to the oomycete pathogen Hyaloperonospora arabidopsidis Noco2. Via map-based cloning and Illumina sequencing, it was determined that the muse9 mutation is in the gene encoding the SWI/SNF chromatin remodeler SYD (SPLAYED), and was thus renamed syd-10. The syd-10 single mutant has no observable alteration from wild-type-like resistance, although the syd-4 T-DNA insertion allele displays enhanced resistance to the bacterial pathogen Pseudomonas syringae pv. maculicola ES4326. Transcription of SNC1 is increased in both syd-4 and syd-10. These data suggest that SYD plays a subtle, specific role in the regulation of SNC1 expression and SNC1-mediated immunity. SYD may work with other proteins at the chromatin level to repress SNC1 transcription; such regulation is important for fine-tuning the expression of NLR-encoding genes to prevent unpropitious autoimmunity.
Keywords: Cell Biology; Plant Science; Physiology; General Medicine

Cancer/Testis antigen PASD1 silences the circadian clock - Michael, Alicia Kathleen; Harvey, Stacy L.; Sammons, Patrick J.; Anderson, Amanda P.; Kopalle, Hema M.; Banham, Alison H.; Partch, Carrie L. (Molecular Cell)
The circadian clock orchestrates global changes in transcriptional regulation on a daily basis via the bHLH-PAS transcription factor CLOCK:BMAL1. Pathways driven by other bHLH-PAS transcription factors have a homologous repressor that modulates activity on a tissue-specific basis, but none have been identified for CLOCK:BMAL1. We show here that the cancer/testis antigen PASD1 fulfills this role to suppress circadian rhythms. PASD1 is evolutionarily related to CLOCK and interacts with the CLOCK:BMAL1 complex to repress transcriptional activation. Expression of PASD1 is restricted to germline tissues in healthy individuals but can be induced in cells of somatic origin upon oncogenic transformation. Reducing PASD1 in human cancer cells significantly increases the amplitude of transcriptional oscillations to generate more robust circadian rhythms. Our results describe a function for a germline-specific protein in regulation of the circadian clock and provide a molecular link from oncogenic transformation to suppression of circadian rhythms.
Keywords: Cell Biology; Molecular Biology

Nup50 is required for cell differentiation and exhibits transcription-dependent dynamics - Buchwalter, Abigail L.; Liang, Yun; HETZER, Martin W (Molecular Biology of the Cell)
The nuclear pore complex (NPC) plays a critical role in gene expression by mediating import of transcription regulators into the nucleus and export of RNA transcripts to the cytoplasm. Emerging evidence suggests that in addition to mediating transport, a subset of nucleoporins (Nups) engage in transcriptional activation and elongation at genomic loci that are not associated with NPCs. The underlying mechanism and regulation of Nup mobility on and off nuclear pores remain unclear. Here we show that Nup50 is a mobile Nup with a pronounced presence both at the NPC and in the nucleoplasm that can move between these different localizations. Strikingly, the dynamic behavior of Nup50 in both locations is dependent on active transcription by RNA polymerase II and requires the N-terminal half of the protein, which contains importin α– and Nup153-binding domains. However, Nup50 dynamics are independent of importin α, Nup153, and Nup98, even though the latter two proteins also exhibit transcription-dependent mobility. Of interest, depletion of Nup50 from C2C12 myoblasts does not affect cell proliferation but inhibits differentiation into myotubes. Taken together, our results suggest a transport-independent role for Nup50 in chromatin biology that occurs away from the NPC.
Keywords: Cell Biology; Molecular Biology

Breaching the nuclear envelope in development and disease - Hatch, Emily; HETZER, Martin W (Journal of Cell Biology)
In eukaryotic cells the nuclear genome is enclosed by the nuclear envelope (NE). In metazoans, the NE breaks down in mitosis and it has been assumed that the physical barrier separating nucleoplasm and cytoplasm remains intact during the rest of the cell cycle and cell differentiation. However, recent studies suggest that nonmitotic NE remodeling plays a critical role in development, virus infection, laminopathies, and cancer. Although the mechanisms underlying these NE restructuring events are currently being defined, one common theme is activation of protein kinase C family members in the interphase nucleus to disrupt the nuclear lamina, demonstrating the importance of the lamina in maintaining nuclear integrity.
Keywords: Cell Biology

The role of Nup98 in transcription regulation in healthy and diseased cells - Franks, Tobias M.; HETZER, Martin W (Trends in Cell Biology)
Nuclear pore complex (NPC) proteins are known for their critical roles in regulating nucleocytoplasmic traffic of macromolecules across the nuclear envelope. However, recent findings suggest that some nucleoporins (Nups), including Nup98, have additional functions in developmental gene regulation. Nup98, which exhibits transcription-dependent mobility at the NPC but can also bind chromatin away from the nuclear envelope, is frequently involved in chromosomal translocations in a subset of patients suffering from acute myeloid leukemia (AML). A common paradigm suggests that Nup98 translocations cause aberrant transcription when they are recuited to aberrant genomic loci. Importantly, this model fails to account for the potential loss of wild type (WT) Nup98 function in the presence of Nup98 translocation mutants. Here we examine how the cell might regulate Nup98 nucleoplasmic protein levels to control transcription in healthy cells. In addition, we discuss the possibility that dominant negative Nup98 fusion proteins disrupt the transcriptional activity of WT Nup98 in the nucleoplasm to drive AML.
Keywords: Cell Biology

Protein homeostasis: Live long, won't prosper - Toyama, Brandon H.; HETZER, Martin W (Nature Reviews Molecular Cell Biology)
Protein turnover is an effective way of maintaining a functional proteome, as old and potentially damaged polypeptides are destroyed and replaced by newly synthesized copies. An increasing number of intracellular proteins, however, have been identified that evade this turnover process and instead are maintained over a cell's lifetime. This diverse group of long-lived proteins might be particularly prone to accumulation of damage and thus have a crucial role in the functional deterioration of key regulatory processes during ageing.
Keywords: Cell Biology; Molecular Biology

Outfits for different occasions: tissue-specific roles of Nuclear Envelope proteins - Gomez-Cavazos, J Sebastian; HETZER, Martin W (Current Opinion in Cell Biology)
The Nuclear Envelope (NE) contains over 100 different proteins that associate with nuclear components such as chromatin, the lamina and the transcription machinery. Mutations in genes encoding NE proteins have been shown to result in tissue-specific defects and disease, suggesting cell-type specific differences in NE composition and function. Consistent with these observations, recent studies have revealed unexpected functions for numerous NE associated proteins during cell differentiation and development. Here we review the latest insights into the roles played by the NE in cell differentiation, development, disease and aging, focusing primarily on inner nuclear membrane (INM) proteins and nuclear pore components.
Keywords: Cell Biology

Transient nuclear envelope rupturing during interphase in human cancer cells - Vargas, Jesse D.; Hatch, Emily M.; Anderson, Daniel J.; HETZER, Martin W (Nucleus)
Neoplastic cells are often characterized by specific morphological abnormalities of the nuclear envelope (NE), which have been used for cancer diagnosis for more than a century. The NE is a double phospholipid bilayer that encapsulates the nuclear genome, regulates all nuclear trafficking of RNAs and proteins and prevents the passive diffusion of macromolecules between the nucleoplasm and the cytoplasm. Whether there is a consequence to the proper functioning of the cell and loss of structural integrity of the nucleus remains unclear. Using live cell imaging, we characterize a phenomenon wherein nuclei of several proliferating human cancer cell lines become temporarily ruptured during interphase. Strikingly, NE rupturing was associated with the mislocalization of nucleoplasmic and cytoplasmic proteins and, in the most extreme cases, the entrapment of cytoplasmic organelles in the nuclear interior. In addition, we observed the formation of micronuclei-like structures during interphase and the movement of chromatin out of the nuclear space. The frequency of these NE rupturing events was higher in cells in which the nuclear lamina, a network of intermediate filaments providing mechanical support to the NE, was not properly formed. Our data uncover the existence of a NE instability that has the potential to change the genomic landscape of cancer cells.
Keywords: Cell Biology

A change in nuclear pore complex composition regulates cell differentiation - D'Angelo, Maximiliano A.; Gomez-Cavazos, J. Sebastian; Mei, Arianna; Lackner, Daniel H.; HETZER, Martin W (Developmental Cell)
Nuclear pore complexes (NPCs) are built from ∼30 different proteins called nucleoporins or Nups. Previous studies have shown that several Nups exhibit cell-type-specific expression and that mutations in NPC components result in tissue-specific diseases. Here we show that a specific change in NPC composition is required for both myogenic and neuronal differentiation. The transmembrane nucleoporin Nup210 is absent in proliferating myoblasts and embryonic stem cells (ESCs) but becomes expressed and incorporated into NPCs during cell differentiation. Preventing Nup210 production by RNAi blocks myogenesis and the differentiation of ESCs into neuroprogenitors. We found that the addition of Nup210 to NPCs does not affect nuclear transport but is required for the induction of genes that are essential for cell differentiation. Our results identify a single change in NPC composition as an essential step in cell differentiation and establish a role for Nup210 in gene expression regulation and cell fate determination.
Keywords: Developmental Biology; Cell Biology; General Biochemistry; Genetics and Molecular Biology; Molecular Biology

POM121 and Sun1 play a role in early steps of interphase NPC assembly - Talamas, Jessica A.; HETZER, Martin W (Journal of Cell Biology)
Nuclear pore complexes (NPCs) assemble at the end of mitosis during nuclear envelope (NE) reformation and into an intact NE as cells progress through interphase. Although recent studies have shown that NPC formation occurs by two different molecular mechanisms at two distinct cell cycle stages, little is known about the molecular players that mediate the fusion of the outer and inner nuclear membranes to form pores. In this paper, we provide evidence that the transmembrane nucleoporin (Nup), POM121, but not the Nup107–160 complex, is present at new pore assembly sites at a time that coincides with inner nuclear membrane (INM) and outer nuclear membrane (ONM) fusion. Overexpression of POM121 resulted in juxtaposition of the INM and ONM. Additionally, Sun1, an INM protein that is known to interact with the cytoskeleton, was specifically required for interphase assembly and localized with POM121 at forming pores. We propose a model in which POM121 and Sun1 interact transiently to promote early steps of interphase NPC assembly.
Keywords: Cell Biology

Functional interactions between nucleoporins and chromatin - Liang, Yun; HETZER, Martin W (Current Opinion in Cell Biology)
As the gatekeepers of the eukaryotic cell nucleus, nuclear pore complexes (NPCs) mediate all molecular trafficking between the nucleoplasm and the cytoplasm. In recent years, transport-independent functions of NPC components, nucleoporins, have been identified including roles in chromatin organization and gene regulation. Here, we summarize our current view of the NPC as a dynamic hub for the integration of chromatin regulation and nuclear trafficking and discuss the functional interplay between nucleoporins and the nuclear genome.
Keywords: Cell Biology

Editorial overview - HETZER, Martin W; Cavalli, Giacomo (Current Opinion in Cell Biology)
Keywords: Cell Biology

The role of the nuclear pore complex in aging of post-mitotic cells - HETZER, Martin W (Aging)
Keywords: Cell Biology; Aging

Native-unlike long-lived intermediates along the folding pathway of the amyloidogenic protein β2-Microglobulin revealed by real-time two-dimensional NMR - Corazza, Alessandra; Rennella, Enrico; Schanda, Paul; Mimmi, Maria Chiara; Cutuil, Thomas; Raimondi, Sara; Giorgetti, Sofia; Fogolari, Federico; Viglino, Paolo; Frydman, Lucio; Gal, Maayan; Bellotti, Vittorio; et al. (Journal of Biological Chemistry)
β2-microglobulin (β2m), the light chain of class I major histocompatibility complex, is responsible for the dialysis-related amyloidosis and, in patients undergoing long term dialysis, the full-length and chemically unmodified β2m converts into amyloid fibrils. The protein, belonging to the immunoglobulin superfamily, in common to other members of this family, experiences during its folding a long-lived intermediate associated to the trans-to-cis isomerization of Pro-32 that has been addressed as the precursor of the amyloid fibril formation. In this respect, previous studies on the W60G β2m mutant, showing that the lack of Trp-60 prevents fibril formation in mild aggregating condition, prompted us to reinvestigate the refolding kinetics of wild type and W60G β2m at atomic resolution by real-time NMR. The analysis, conducted at ambient temperature by the band selective flip angle short transient real-time two-dimensional NMR techniques and probing the β2m states every 15 s, revealed a more complex folding energy landscape than previously reported for wild type β2m, involving more than a single intermediate species, and shedding new light into the fibrillogenic pathway. Moreover, a significant difference in the kinetic scheme previously characterized by optical spectroscopic methods was discovered for the W60G β2m mutant.
Keywords: Cell Biology; Biochemistry; Molecular Biology

Border control at the nucleus: Biogenesis and organization of the nuclear membrane and pore complexes - HETZER, Martin W; Wente, Susan R. (Developmental Cell)
Over the last decade, the nuclear envelope (NE) has emerged as a key component in the organization and function of the nuclear genome. As many as 100 different proteins are thought to specifically localize to this double membrane that separates the cytoplasm and the nucleoplasm of eukaryotic cells. Selective portals through the NE are formed at sites where the inner and outer nuclear membranes are fused, and the coincident assembly of ∼30 proteins into nuclear pore complexes occurs. These nuclear pore complexes are essential for the control of nucleocytoplasmic exchange. Many of the NE and nuclear pore proteins are thought to play crucial roles in gene regulation and thus are increasingly linked to human diseases.
Keywords: Developmental Biology; Cell Biology; General Biochemistry; Genetics and Molecular Biology; Molecular Biology

Recruitment of functionally distinct membrane proteins to chromatin mediates nuclear envelope formation in vivo - Anderson, Daniel J.; Vargas, Jesse D.; Hsiao, Joshua P.; HETZER, Martin W (Journal of Cell Biology)
Formation of the nuclear envelope (NE) around segregated chromosomes occurs by the reshaping of the endoplasmic reticulum (ER), a reservoir for disassembled nuclear membrane components during mitosis. In this study, we show that inner nuclear membrane proteins such as lamin B receptor (LBR), MAN1, Lap2β, and the trans-membrane nucleoporins Ndc1 and POM121 drive the spreading of ER membranes into the emerging NE via their capacity to bind chromatin in a collaborative manner. Despite their redundant functions, decreasing the levels of any of these trans-membrane proteins by RNAi-mediated knockdown delayed NE formation, whereas increasing the levels of any of them had the opposite effect. Furthermore, acceleration of NE formation interferes with chromosome separation during mitosis, indicating that the time frame over which chromatin becomes membrane enclosed is physiologically relevant and regulated. These data suggest that functionally distinct classes of chromatin-interacting membrane proteins, which are present at nonsaturating levels, collaborate to rapidly reestablish the nuclear compartment at the end of mitosis.
Keywords: Cell Biology

ER membrane–bending proteins are necessary for de novo nuclear pore formation - Dawson, T. Renee; Lazarus, Michelle D.; HETZER, Martin W; Wente, Susan R. (Journal of Cell Biology)
Nucleocytoplasmic transport occurs exclusively through nuclear pore complexes (NPCs) embedded in pores formed by inner and outer nuclear membrane fusion. The mechanism for de novo pore and NPC biogenesis remains unclear. Reticulons (RTNs) and Yop1/DP1 are conserved membrane protein families required to form and maintain the tubular endoplasmic reticulum (ER) and the postmitotic nuclear envelope. In this study, we report that members of the RTN and Yop1/DP1 families are required for nuclear pore formation. Analysis of Saccharomyces cerevisiae prp20-G282S and nup133Δ NPC assembly mutants revealed perturbations in Rtn1–green fluorescent protein (GFP) and Yop1-GFP ER distribution and colocalization to NPC clusters. Combined deletion of RTN1 and YOP1 resulted in NPC clustering, nuclear import defects, and synthetic lethality with the additional absence of Pom34, Pom152, and Nup84 subcomplex members. We tested for a direct role in NPC biogenesis using Xenopus laevis in vitro assays and found that anti-Rtn4a antibodies specifically inhibited de novo nuclear pore formation. We hypothesize that these ER membrane–bending proteins mediate early NPC assembly steps.
Keywords: Cell Biology

Reshaping of the endoplasmic reticulum limits the rate for nuclear envelope formation - Anderson, Daniel J.; HETZER, Martin W (Journal of Cell Biology)
During mitosis in metazoans, segregated chromosomes become enclosed by the nuclear envelope (NE), a double membrane that is continuous with the endoplasmic reticulum (ER). Recent in vitro data suggest that NE formation occurs by chromatin-mediated reorganization of the tubular ER; however, the basic principles of such a membrane-reshaping process remain uncharacterized. Here, we present a quantitative analysis of nuclear membrane assembly in mammalian cells using time-lapse microscopy. From the initial recruitment of ER tubules to chromatin, the formation of a membrane-enclosed, transport-competent nucleus occurs within ∼12 min. Overexpression of the ER tubule-forming proteins reticulon 3, reticulon 4, and DP1 inhibits NE formation and nuclear expansion, whereas their knockdown accelerates nuclear assembly. This suggests that the transition from membrane tubules to sheets is rate-limiting for nuclear assembly. Our results provide evidence that ER-shaping proteins are directly involved in the reconstruction of the nuclear compartment and that morphological restructuring of the ER is the principal mechanism of NE formation in vivo.
Keywords: Cell Biology

Structure, dynamics and function of nuclear pore complexes - D’Angelo, Maximiliano A.; HETZER, Martin W (Trends in Cell Biology)
Nuclear pore complexes are large aqueous channels that penetrate the nuclear envelope, thereby connecting the nuclear interior with the cytoplasm. Until recently, these macromolecular complexes were viewed as static structures, the only function of which was to control the molecular trafficking between the two compartments. It has now become evident that this simplistic scenario is inaccurate and that nuclear pore complexes are highly dynamic multiprotein assemblies involved in diverse cellular processes ranging from the organization of the cytoskeleton to gene expression. In this review, we discuss the most recent developments in the nuclear-pore-complex field, focusing on the assembly, disassembly, maintenance and function of this macromolecular structure.
Keywords: Cell Biology

Reorganization of the nuclear envelope during open mitosis - Kutay, Ulrike; HETZER, Martin W (Current Opinion in Cell Biology)
The nuclear envelope (NE) provides a selective barrier between the nuclear interior and the cytoplasm and constitutes a central component of intracellular architecture. During mitosis in metazoa, the NE breaks down leading to the complete mixing of the nuclear content with the cytosol. Interestingly, many NE components actively participate in mitotic progression. After chromosome segregation, the NE is reassembled around decondensing chromatin and the nuclear compartment is reestablished in the daughter cells. Here, we summarize recent progress in deciphering the molecular mechanisms underlying NE dynamics during cell division.
Keywords: Cell Biology

The life cycle of the metazoan nuclear envelope - Anderson, Daniel J; HETZER, Martin W (Current Opinion in Cell Biology)
The nuclear envelope is a double-layered membrane that encloses the nuclear genome and transcriptional machinery. In dividing cells of metazoa, the nucleus completely disassembles during mitosis, creating the need to re-establish the nuclear compartment at the end of each cell division. Given the crucial role of the nuclear envelope in gene regulation and cellular organization, it is not surprising that its biogenesis and organization have become active research areas. We will review recent insights into nuclear membrane dynamics during the cell cycle.
Keywords: Cell Biology

Shaping the endoplasmic reticulum into the nuclear envelope - Anderson, Daniel J.; HETZER, Martin W (Journal of Cell Science)
The nuclear envelope (NE), a double membrane enclosing the nucleus of eukaryotic cells, controls the flow of information between the nucleoplasm and the cytoplasm and provides a scaffold for the organization of chromatin and the cytoskeleton. In dividing metazoan cells, the NE breaks down at the onset of mitosis and then reforms around segregated chromosomes to generate the daughter nuclei. Recent data from intact cells and cell-free nuclear assembly systems suggest that the endoplasmic reticulum (ER) is the source of membrane for NE assembly. At the end of mitosis, ER membrane tubules are targeted to chromatin via tubule ends and reorganized into flat nuclear membrane sheets by specific DNA-binding membrane proteins. In contrast to previous models, which proposed vesicle fusion to be the principal mechanism of NE formation, these new studies suggest that the nuclear membrane forms by the chromatin-mediated reshaping of the ER.
Keywords: Cell Biology

Nuclear envelope formation by chromatin-mediated reorganization of the endoplasmic reticulum - Anderson, Daniel J.; HETZER, Martin W (Nature Cell Biology)
The formation of the nuclear envelope (NE) around chromatin is a major membrane-remodelling event that occurs during cell division of metazoa. It is unclear whether the nuclear membrane reforms by the fusion of NE fragments or if it re-emerges from an intact tubular network of the endoplasmic reticulum (ER). Here, we show that NE formation and expansion requires a tubular ER network and occurs efficiently in the presence of the membrane fusion inhibitor GTPγS. Chromatin recruitment of membranes, which is initiated by tubule-end binding, followed by the formation, expansion and sealing of flat membrane sheets, is mediated by DNA-binding proteins residing in the ER. Thus, chromatin plays an active role in reshaping of the ER during NE formation.
Keywords: Cell Biology

The role of the nuclear envelope in cellular organization - D’Angelo, M. A.; HETZER, Martin W (Cellular and Molecular Life Sciences)
Over the last years it has become evident that the nuclear envelope (NE) is more than a passive membrane barrier that separates the nucleus from the cytoplasm. The NE not only controls the trafficking of macromolecules between the nucleoplasm and the cytosol, but also provides anchoring sites for chromosomes and cytoskeleton to the nuclear periphery. Targeting of chromatin to the NE might actually be part of gene expression regulation in eukaryotes. Mutations in certain NE proteins are associated with a diversity of human diseases, including muscular dystrophy, neuropathy, lipodistrophy, torsion dystonia and the premature aging condition progeria. Despite the importance of the NE for cell division and differentiation, relatively little is known about its biogenesis and its role in human diseases. It is our goal to provide a comprehensive view of the NE and to discuss possible implications of NE-associated changes for gene expression, chromatin organization and signal transduction.
Keywords: Cell Biology; Cellular and Molecular Neuroscience; Pharmacology; Molecular Biology; Molecular Medicine

Pushing the envelope: Structure, function, and dynamics of the nuclear periphery - HETZER, Martin W; Walther, Tobias C.; Mattaj, Iain W. (Annual Review of Cell and Developmental Biology)
The nuclear envelope (NE) is a highly specialized membrane that delineates the eukaryotic cell nucleus. It is composed of the inner and outer nuclear membranes, nuclear pore complexes (NPCs) and, in metazoa, the lamina. The NE not only regulates the trafficking of macromolecules between nucleoplasm and cytosol but also provides anchoring sites for chromatin and the cytoskeleton. Through these interactions, the NE helps position the nucleus within the cell and chromosomes within the nucleus, thereby regulating the expression of certain genes. The NE is not static, rather it is continuously remodeled during cell division. The most dramatic example of NE reorganization occurs during mitosis in metazoa when the NE undergoes a complete cycle of disassembly and reformation. Despite the importance of the NE for eukaryotic cell life, relatively little is known about its biogenesis or many of its functions. We thus are far from understanding the molecular etiology of a diverse group of NE-associated diseases.
Keywords: Cell Biology; Developmental Biology

The Ran GTPase as a marker of chromosome position in spindle formation and nuclear envelope assembly - HETZER, Martin W; Gruss, Oliver J.; Mattaj, Iain W. (Nature Cell Biology)
The small GTPase Ran is a key regulator of nucleocytoplasmic transport during interphase. The asymmetric distribution of the GTP-bound form of Ran across the nuclear envelope — that is, large quantities in the nucleus compared with small quantities in the cytoplasm — determines the directionality of many nuclear transport processes. Recent findings that Ran also functions in spindle formation and nuclear envelope assembly during mitosis suggest that Ran has a general role in chromatin-centred processes. Ran functions in these events as a signal for chromosome position.
Keywords: Cell Biology

ICln Ion channel splice variants in Caenorhabditis elegans - Fürst, Johannes; Ritter, Markus; Rudzki, Jakob; Danzl, Johann G; Gschwentner, Martin; Scandella, Elke; Jakab, Martin; König, Matthias; Oehl, Bernhard; Lang, Florian; Deetjen, Peter; Paulmichl, Markus (Journal of Biological Chemistry)
ICln is an ion channel identified by expression cloning using a cDNA library from Madin-Darby canine kidney cells. In all organisms tested so far, only one transcript for the ICln protein could be identified. Here we show that two splice variants of the ICln ion channel can be found in Caenorhabditis elegans. Moreover, we show that these two splice variants of the ICln channel protein, which we termed IClnN1 and IClnN2, can be functionally reconstituted and tested in an artificial lipid bilayer. In these experiments, the IClnN1-induced currents showed no voltage-dependent inactivation, whereas the IClnN2-induced currents fully inactivated at positive potentials. The molecular entity responsible for the voltage-dependent inactivation of IClnN2 is a cluster of positively charged amino acids encoded by exon 2a, which is absent in IClnN1. Our experiments suggest a mechanism of channel inactivation that is similar to the “ball and chain” model proposed for the Shaker potassium channel,i.e. a cluster of positively charged amino acids hinders ion permeation through the channel by a molecular and voltage-dependent interaction at the inner vestibulum of the pore. This hypothesis is supported by the finding that synthetic peptides with the same amino acid sequence as the positive cluster can transform the IClnN1-induced current to the current observed after reconstitution of IClnN2. Furthermore, we show that the nematode ICln gene is embedded in an operon harboring two additional genes, which we termed Nx and Ny. Co-reconstitution of Nx and IClnN2 and functional analysis of the related currents revealed a functional interaction between the two proteins, as evidenced by the fact that the IClnN2-induced current in the presence of Nx was no longer voltage-sensitive. The experiments described indicate that the genome organization in nematodes allows an effective approach for the identification of functional partner proteins of ion channels.
Keywords: Cell Biology; Molecular Biology; Biochemistry

Distinct AAA-ATPase p97 complexes function in discrete steps of nuclear assembly - HETZER, Martin W; Meyer, Hemmo H.; Walther, Tobias C.; Bilbao-Cortes, Daniel; Warren, Graham; Mattaj, Iain W. (Nature Cell Biology)
Although nuclear envelope (NE) assembly is known to require the GTPase Ran, the membrane fusion machinery involved is uncharacterized. NE assembly involves formation of a reticular network on chromatin, fusion of this network into a closed NE and subsequent expansion. Here we show that p97, an AAA-ATPase previously implicated in fusion of Golgi and transitional endoplasmic reticulum (ER) membranes together with the adaptor p47, has two discrete functions in NE assembly. Formation of a closed NE requires the p97–Ufd1–Npl4 complex, not previously implicated in membrane fusion. Subsequent NE growth involves a p97–p47 complex. This study provides the first insights into the molecular mechanisms and specificity of fusion events involved in NE formation.
Keywords: Cell Biology

An Atp-dependent, Ran-independent mechanism for nuclear import of the U1a and U2b′′ spliceosome proteins - HETZER, Martin W; Mattaj, Iain W. (Journal of Cell Biology)
Nuclear import of the two uracil-rich small nuclear ribonucleoprotein (U snRNP) components U1A and U2B′′ is mediated by unusually long and complex nuclear localization signals (NLSs). Here we investigate nuclear import of U1A and U2B′′ in vitro and demonstrate that it occurs by an active, saturable process. Several lines of evidence suggest that import of the two proteins occurs by an import mechanism different to those characterized previously. No cross competition is seen with a variety of previously studied NLSs. In contrast to import mediated by members of the importin-β family of nucleocytoplasmic transport receptors, U1A/U2B′′ import is not inhibited by either nonhydrolyzable guanosine triphosphate (GTP) analogues or by a mutant of the GTPase Ran that is incapable of GTP hydrolysis. Adenosine triphosphate is capable of supporting U1A and U2B′′ import, whereas neither nonhydrolyzable adenosine triphosphate analogues nor GTP can do so. U1A and U2B′′ import in vitro does not require the addition of soluble cytosolic proteins, but a factor or factors required for U1A and U2B′′ import remains tightly associated with the nuclear fraction of conventionally permeabilized cells. This activity can be solubilized in the presence of elevated MgCl2. These data suggest that U1A and U2B′′ import into the nucleus occurs by a hitherto uncharacterized mechanism.
Keywords: Cell Biology

GTP hydrolysis by Ran is required for nuclear envelope assembly - HETZER, Martin W; Bilbao-Cortés, Daniel; Walther, Tobias C; Gruss, Oliver J; Mattaj, Iain W (Molecular Cell)
Nuclear formation in Xenopus egg extracts requires cytosol and is inhibited by GTPγS, indicating a requirement for GTPase activity. Nuclear envelope (NE) vesicle fusion is extensively inhibited by GTPγS and two mutant forms of the Ran GTPase, Q69L and T24N. Depletion of either Ran or RCC1, the exchange factor for Ran, from the assembly reaction also inhibits this step of NE formation. Ran depletion can be complemented by the addition of Ran loaded with either GTP or GDP but not with GTPγS. RCC1 depletion is only complemented by RCC1 itself or by RanGTP. Thus, generation of RanGTP by RCC1 and GTP hydrolysis by Ran are both required for the extensive membrane fusion events that lead to NE formation.
Keywords: Cell Biology; Molecular Biology